Tactical citizenships: Encounters with everyday state in the Republic of Cyprus - Kouros, Theodoros (My University, 2024)
The idea of citizenship is formed through a dynamic and flexible set of relationships that go beyond a sequence of formal rights and duties. It is recurring in everyday social contexts-in practices that play out in the real world, in the everyday exercises or refusals of citizenship rights, in the purposeful defiance of norms, and in the tactical evasion of duties. This book explores the troubled relationship between a state and its citizens across four different kinds of social spaces in Limassol, Cyprus. Tactical Citizenships is a testament to the tenacity and resourcefulness of citizens of unfair states in directing their relations with the government.
Keywords: Citizenships; Political anthropology; Republic of Cyprus; Citizenship rights